Provider Perceptions of Medication for Opioid Used Disorder (Moud): A Qualitative Study in Communities with High Opioid Overdose Death Rates. Issue 1 (December 2022) - Paul, Nicole; Kennedy, Amy J.; Taubenberger, Simone; Chang, Judy C.; Hacker, Karen
Background: Medication for Opioid Use Disorder (MOUD) has been shown to be a safe, cost-effective intervention that successfully lowers risk of opioid overdose. However, access to and use of MOUD has been limited. Our objective was to explore attitudes, opinions, and beliefs regarding MOUD among healthcare and social service providers in a community highly impacted by the opioid overdose epidemic. Methods: As part of a larger ethnographic study examining neighborhoods in Allegheny County, PA, with the highest opioid overdose death rates, semi-structured qualitative in-person and telephone interviews were conducted with forty-five providers treating persons with opioid use disorders in these communities. An open coding approach was used to code interview transcripts followed by thematic analysis. Results: Three major themes were identified related to MOUD from the perspectives of our provider participants. Within a variety of health and substance use service roles and settings, provider reflections revealed: (1) different opinions about MOUD as a transition to abstinence or as a long-term treatment; (2) perceived lack of uniformity and dissemination of accurate information of MOUD care, permitting differences in care, and (3) observed barriers to entry and navigation of MOUD, including referrals as a "word-of-mouth insider system" and challenges of getting patients MOUD services when they need it. Conclusions: Even in communities hard hit by the opioid overdose epidemic, healthcare providers' disagreement about the standard of care for MOUD can be a relevant obstacle. These insights can inform efforts to improve MOUD treatment and access for people with opioid use disorders.